MANAJEMEN PERGURUAN TINGGI BERBASIS NILAI-NILAI PESANTREN (Kajian Pemikiran Alternatif) - Mardiyah, - - (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
Pathology bureaucracy syndrome that continues to infect the world of education in Indonesia resulted in the formulation of management education does not find appropriate and relevant in the midst of poor quality and the quality of education. Proven innovation and improvement efforts as well as the management education system ranging from education decentralization and school autonomy and school-based management (SBM), which have been initiated by the government was unable so far to increase the quality of national education. Finally, it happens competitiveness of our educational output relatively weak compared to other countries. Planning to convert the values of the pesantren as theology and base management alternative education course departed from the presence of 'deadlock' national education system to print the human resources quality as a result of the multidimensional crisis has hit Indonesia. The moral and identity crises that continue to color the behavior of the nation's elite in particular and the whole society in general have attacked them. With values based boarding school, it is expected that the principles of struggles, devotion, sacrifice, jihad, ijtihad, and Mujahadah inspired by the values of sincerity, simplicity, confidence and independence, brotherhood and togetherness as well as the freedom to think positive and productive be the mainstay of management education and development of various types of education that is managed in it. Keywords: bureaucracy, decentralization, pesantren